ANALISIS KONTRIBUSI DAN BREAK EVEN POINT (BEP) USAHATAHI PEPAYA CALIFORNIA DI KECAMATAN BUANA PEMACA KABUPATEN OKUS - Dayu Widyanti; Munajat; Fifian Permata Sari (Media Bina Ilmiah, 2022)
This study aims to analyze the contribution and break even point (BEP) of California papaya farming in Buana Pemaca District, South OKU Regency. The method used in this study is the survey method, the sampling method used is the simple random sampling method with a sample size of 142 people. The results of the study showed an average contribution of 78.92%. This means that 78.92% of California papaya farming has a high contribution to the total family income in Buana Pemaca District, South OKU Regency. The results of the Break Even Point analysis show that the results of California papaya farming are 6,804.56, which means that it is greater than the amount of production, meaning that the business is feasible.